«Սարոյանականը» և Վ. Սարոյանի թատերագրության ընդհանուր գծերը - Ա. Գ. Ասլիբեկյան (ՀՀ ԳԱԱ հրատ.)
В. Сароян в целом не смирился с американским театром. Он считал, что американский театр давно утратил театральность, заменив ее достоверностью натуралистических деталей и бытом. Saroyan was intransigent with the American theater in general. He always found that it has lost its “theatricalism” and game, which was replaced by the accuracy of naturalistic elements and everyday life.
Keywords: Literature; Language and Literature; PN2000 Dramatic representation; The Theater